An Inverse Sturin-Liouviile Problem for a Hill's Equation - Tuz, Munevver (Soc Paranaense Matematica, 2014)
In this paper, we consider Hill's equation -y + g(x)y = lambda y, where q is an element of L-1 [0,pi]. A Hill equation defined on a semi-infinite interval will in general have a mixed spectrum. The continuous spectrum will in general consist of an infinite number of disjoint finite intervals. Between these intervals, point eigenval ties can exist. It is shown that under suitable hypotheses on the spectrum a full knowledge of the spectrum leads to a unique determination of the potential function in the Hill's equation. Moreover, it is shown here that if q(x) is prescribed over the interval [pi/2, pi]then a single spectrum suffices to determined q(r) on the interval [0, pi/2].
Keywords: Hill's equation; inverse problem; spectrum; potential; uniqueness